Application of off-the-shelf stereo-cameras for the 3D assessment of morphometric variations caused by rhinoplasty. (3rd April 2017) - Galantucci, Luigi Maria; Lavecchia, Fulvio; Pastore, Patrizia; Percoco, Gianluca
Abstract: The present paper shows how a non-invasive and low-cost photogrammetric stereo device allows the assessment of morphometric variations of the nose following rhinoplasty. Six female patients, aged between 24 and 37 years, underwent 3D stereo-photogrammetric scanning. Three-dimensional computerised models were generated, extracting also information related to the coordinates of facial landmarks, distances between landmarks, angles, in pre- and postoperative situation. Two kinds of analysis were carried out: (i) statistical correlation between size variations and (ii) morphometric analysis, including General Procrustes Analysis (GPA), Principal Components Analysis (PCA) and Warping. The study shows the usefulness of the stereo-photogrammetric facial digitisation for morphometric analysis of the human face. Three-dimensional computerised models are also an important tool for the assessment of the surgeon's performance in the event of dispute between doctor and patient. Moreover, confirmation of the PCA as an analytical tool for the identification of components characterising the morphometric structure of the nose is highlighted.